Fe modeling of shock waves - Syla, Naim; Dalipi, Bashkim; Aliaj, Fisnik; Syla, Dhurata (International Journal of Computational and Experimental Science and Engineering, 2024)
Among the well-known methods in medicine is the application of mechanical waves, as well as ultrasound and shock wave methods. It is known that the characteristics of mechanical waves are determined by amplitude and frequency. If the frequency of the wave is above 20000Hz, then it cannot be heard by the human ear. These waves are called ultrasounds. The basic principle of ultrasound application in medicine is that different tissues or foreign bodies (eg. stones) reflect ultrasound waves differently. In ultrasonography, reflected ultrasound waves are recorded by transducers and translated into a recorded image. On the other hand, if the mechanical wave propagates through a medium with a speed greater than the speed of sound propagated through that medium, then we have the shock wave. In this case, the waves produce an instantaneous increase in pressure or energy for very short intervals of time. These energetic impulses are usually applied in medicine to break kidney stones or urinary channels stones. The basic principle of the application is to focus the energy impulse of the wave on the places where the stones are found and hit them. During shock, the stones are broken and these can come out through the urinary channels. Such a method is called lithotripsy, while the device is called a lithotripter. In this contribution, we modelled the shock waves according to the FE method, while the simulation was done in the ANSYS application.